IS THE ‘SAATLERİ AYARLAMA ENSTİTÜSÜ’ AN IRONIC-TONGUED WORK? - Servet KARÇIĞA (Fırat University, 2019)
The novel named as Saatleri Ayarlama Enstitüsü, published as a book by Ahmet Hamdi Tanpınar at a time close to his death, comes at the beginning of the works among the ones which received the most various appreciation in Turkish literature. The reasons of different appreciations and perspectives made for this work arise from the complexity of the work. Involvement of many provisions, motifs and symbols and their ingenious use make the understanding and interpretation of the work difficult. Within this difficulty, there are roles of architecture, music, fine arts, bureaucracy, spiritualism, dreams, psychoanalysis, time/hours, sciences (alchemy, history, literature), East-West culture, religion and superstitions issues, all of which are used in a different language/stylistic writing styles in this work that are not so familiar within Turkish literature. This language and style are subject to different evaluations by researchers. When the Institute of Setting Up Watches novel is evaluated, different narrative techniques and concepts such as "satire" (criticism / satire / criticism), "humor", "humor" (funny), "grotesque", "game", "absurd" (nonsensical / ridiculous), "allegory", "irony" are utilized. Irony is a concept lately discovered in Turkish literature. When we look at the studies about irony, it is seen that there was no or little irony if any before 1990 even a few words related with irony were just seen in some articles. After 1990, the quick increase of the works on this concept (e.g., articles, master's theses and doctoral dissertations) is witnessed. Interestingly, the name of Saatleri Ayarlama Enstitüsü is mostly mentioned for irony related evaluations. Is the Saatleri Ayarlama Enstitüsü really an ironic-tongued work? In this study, the answer of the question will be sought as well as who and how evaluated the Institute of Setting Up the Watches will chronologically be presented from the time of the work written to now.